Early Parenting Moderates the Association Between Parental Depression and Neural Reactivity to Rewards and Losses in Offspring. (July 2015) - Kujawa, Autumn; Proudfit, Greg H.; Laptook, Rebecca; Klein, Daniel N.
Children of parents with depression exhibit neural abnormalities in reward processing. Examining contributions of parenting could provide insight into the development of these abnormalities and the etiology of depression. We evaluated whether early parenting moderates the effects of parental depression on a neural measure of reward and loss processing in mid- to late childhood. Parenting was assessed when children were preschoolers. At age 9, children completed an event-related potential assessment, and the feedback negativity (FN) was measured following rewards and losses ( N = 344). Maternal authoritative parenting moderated the effect of maternal depression; among offspring of mothers with histories of depression, low authoritative parenting predicted a blunted FN. Observed maternal positive parenting interacted with paternal depression in a comparable manner, indicating that maternal parenting may buffer the effects of paternal depression. Early parenting may be important in shaping the neural systems involved in reward processing among children at high risk for depression.